Lying Awake at Night: Cardiac Autonomic Activity in Relation to Sleep Onset and Maintenance - Nano, Marina; Fonseca, Pedro; Overeem, Sebastiaan; Vullings, Rik; Aarts, Ronald M. (Frontiers in Neuroscience, 2020)
Insomnia, i.e. difficulties initiating and/or maintaining sleep, is one of the most common sleep disorders. To study underlying mechanisms for insomnia, we studied autonomic activity changes around sleep onset in participants without clinical insomnia but with varying problems with initiating or maintaining sleep quantified as increased sleep onset latency (SOL) and wake after sleep onset (WASO) respectively. Polysomnography and electrocardiography were simultaneously recorded in 176 participants during a single night. Cardiac autonomic activity was assessed using frequency domain analysis of RR intervals and results show that the normalised spectral power in the low frequency band (LFnu) after sleep onset was significantly higher in participants with long SOL compared to participants with short SOL. Furthermore, the normalised spectral power in the high frequency band (HFnu) was significantly lower in participants with long SOL as compared to participants with short SOL over 3 time periods (first 10 minutes in bed intending to sleep, 10 minutes before and 10 minutes after sleep onset). These results suggest that participants with long SOL are more aroused in all three examined time periods when compared to participants with short SOL, especially for young adults (20-40 years). As there is no clear consensus on the cutoff for an increased WASO, we we used a data-driven approach to explore different cutoffs to define short WASO and long WASO groups. LFnu, HFnu and LF/HF differed between the long and the short WASO groups. A higher LFnu and LF/HF and a lower HFnu was observed in participants with long WASO for most cutoffs. The highest effect size was found using the cutoff of 66 min. Our findings suggest that autonomic cardiac activity has predictive value with respect to sleep characteristics pertaining to sleep onset and maintenance